2020
DOI: 10.3390/coatings10070682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2 Sol/Silane Emulsion in Reducing Water and Chloride Ion Penetration in Concrete

Abstract: Here, a new concrete hydrophobic treatment method is developed using SiO2 sol and silane emulsion. The effectiveness of the modification for concrete protection is evaluated through testing water absorption and chloride diffusion. Two types of concrete with different strength grades (C40, C50) are used as the research object. The results show that the water capillary absorption coefficient and chloride ion diffusion coefficient of concrete decrease greatly under the protection of SiO2 sol and silane emulsion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…These results compare favourably with other studies into waterproofing treatments for concrete. For example, Geng et al [30] treated concreate with combinations of 50.5 % silane emulsion and a Nano-SiO 2 preparation made using the sol-gel process. The silane emulsion (600 g/ m 2 ) alone was found to reduce the water absorption coefficient of concrete by 70 %.…”
Section: Determination Of Capillary Water Absorption Of Hardened Conc...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results compare favourably with other studies into waterproofing treatments for concrete. For example, Geng et al [30] treated concreate with combinations of 50.5 % silane emulsion and a Nano-SiO 2 preparation made using the sol-gel process. The silane emulsion (600 g/ m 2 ) alone was found to reduce the water absorption coefficient of concrete by 70 %.…”
Section: Determination Of Capillary Water Absorption Of Hardened Conc...mentioning
confidence: 99%
“…Thus, diatom distribution throughout the biofilm is heterogeneous, with micro-scale variations [21] dependant on surface roughness and microtopography [23]. In addition, physical, chemical and biological changes in the environment also affect diatom communities causing temporal fluctuations in population numbers and distribution [21].To date, research into protective bio-treatments for concrete has considered the use of bacterial calcium carbonate biodeposition [25][26][27][28] or the direct application of laboratorysynthesised nano-silica [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Such coatings can make the concrete resistant to biological inorganic acids and harmful ions. By doing so, the service life of the concrete can be extended, and the infrastructure can remain functional for longer periods of time. Silane materials have been widely used as hydrophobic coatings on concrete facilities. , To protect the surface of concrete blocks, Li et al created a composite coating made of graphene oxide and isobutyltriethoxysilane (IBTS). Experiments on biofouling in the marine tidal zone revealed that the composite coating gave the concrete surface long-lasting hydrophobicity, limiting the attachment of marine microorganisms and successfully suppressing the development of microbial biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete material ratios and microstructures have been optimized. These not only enhance the strength of concrete but also improve the anti-corrosion performance [3]. However, with the development of civil engineering structures towards deep sea and mountainous areas, coupled with the frequent occurrence of global climate extremes, the structured environment has become more complex.…”
Section: Introductionmentioning
confidence: 99%